Propuesta para la implementación de un museo gastronómico en el pueblo mágico de la ciudad de San Gabriel, provincia del Carchi - Ayala Hernández, Anderson Iván (2024)
The city of San Gabriel, recognized as a magical town in 2019, boasts numerous tourist attractions such as the Paluz waterfall, the ancient Arrayanes forest, and the Salado lagoon. Additionally, it has a rich traditional gastronomy, often unknown. The objective of this research is to develop a comprehensive proposal for the implementation of a gastronomic museum in San Gabriel, Carchi province, which promotes the preservation, dissemination, and appreciation of local culinary culture. The methodology is based on documentary techniques, surveys, interviews, and observation. A total of 204 survey responses were received, although the determined sample was 167. Four interviews were conducted with municipal officials, museum administrators, and a university professor. The most representative results include a profile of the potential museum visitor, an inventory of 34 traditional dishes representing the gastronomic cultural heritage of San Gabriel, the continuity of 10 traditional cooking techniques, and the use of various pre-Hispanic and colonial-era utensils. It is concluded that a gastronomic museum is essential for preserving and disseminating the culinary heritage of the region. By celebrating the history, traditions, and local techniques, these museums educate the public and foster an appreciation of food culture and its connection to history, society, and the environment.